APLIKASI CUSTOMER RELATIONSHIP MANAGEMENT MENGGUNAKAN PENDEKATAN FRAMEWORK OF DYNAMIC (STUDI KASUS: PT BINTANG KHARISMA MOTOR BANDAR LAMPUNG) - Syahirul Alim (Universitas Teknokrat Indonesia, 2021)
PT Bintang Kharisma Motor is a Honda dealer engaged in motorbike service located on Jalan Raya Soekarno Hatta 5A Tanjung Seneng, Bandar Lampung. PT Bintang Kharisma Motor has equipment related to motorbike service, which does not have a system for ordering motorbike service orders and there is no system to measure the level of service found at PT Bintang Kharisma Motor. Apart from that, the recording of the purchase and sale of spare parts still uses manual recording so that distorting data on the purchase and sale of spare parts is still deemed inefficient and ineffective. Making reports that are long and deemed ineffective makes researchers want to develop a system at PT Bintang Kharisma Motor. In making the system at PT Bintang Kharisma Motor made with UML diagrams consisting of three diagrams, namely usecase diagrams, activity diagrams, and class diagrams as the initial system design to be made, then programming is made with the PHP programming language according to the existing user interface design. and MySql as database. The system that has been created can help distort sales / service data, purchase and create purchase and sales reports faster than before, and the system helps in processing complaint data, ordering services, and measuring the level of service provided at PT Bintang Kharisma Motor.